THE OPTIMIZATION OF THE HATCHHOLD RELEASE PROGRAM THROUGH COMMUNITY AND TOURIST PARTICIPATION IN NIPAH, NORTH LOMBOK REGENCY - Laily Fitriani Mulyani; Septiana Dwiyanti; Yuliana Asri; Thoy Batun Citra Rahmadani; Damai Diniariwisan; Wastu Ayu Diamahesa (Forum Komunikasi Dosen, 2025)
Turtles are a species that faces the threat of extinction due to habitat degradation, hunting, and marine pollution. North Lombok Regency has a coastal ecosystem that is an important habitat for turtles to lay their eggs, so conservation efforts are crucial. This community service program aims to optimize the release of hatchlings by increasing community and tourist participation as an ecotourism-based conservation strategy. The methods used include conservation education, community involvement in beach patrols, and hatchling releases involving tourists with a local wisdom-based approach. The results of the activities show an increase in community and tourist awareness of the importance of turtle conservation, as evidenced by their increased involvement in nest monitoring and hatchling releases. In addition, this program contributes to local economic growth through conservation-based ecotourism, where communities are starting to get involved in tourism support services. However, there are still challenges in terms of long-term funding and regulations that need to be strengthened to maintain a balance between tourism and conservation activities. In conclusion, a hatchling release program involving communities and tourists can be an effective and sustainable conservation model. With the right strategy, such as increasing education, partnerships with various parties, and supporting regulations, this program can continue to grow and provide ecological and socio-economic benefits for the community in North Lombok Regency.